Effect of particle shape and size on the morphology and optical properties of zinc oxide synthesized by the polyol method. (15th May 2018) - Alves, T.E.P.; Kolodziej, C.; Burda, C.; Franco, A.
Highlights: Polyol method was used to produce zinc oxide nanoparticles through decomposition of zinc acetate. Additional acetate ions influence the preferential growth of the crystal structure, altering the shape. Hydrolysis reaction time is used to control the particle size while retaining the shape. Shape, size, and defects affect optical properties, such as band-gap and photoluminescence. Graphical abstract: Unlabelled Image Abstract: In this study we prepared zinc oxide (ZnO) nanoparticles using the polyol method with zinc acetate and/or sodium acetate in a propylene glycol medium with varied hydrolysis reaction time (10, 60 and 300 min). It was observed that the hydrolysis reaction time and the concentration of acetate ions had a strong effect on the morphology and size of ZnO nanoparticles (NPs). X-ray diffraction (XRD) patterns revealed that all samples crystalized in the typical ZnO wurtzite structure and Rietveld refinement was used to characterize the structure and to suggest a preferential growth. Fourier transformed infrared spectroscopy (FTIR) was performed and showed the typical ZnO band, no impurity signals, as well as differences in A 1 and E 1 vibration modes due to different crystal growth in the structure. Raman scattering was carried out to determine the defects in the structure of ZnO, such as interstitial oxygen and oxygen vacancies. Transmission electron microscope (TEM) images revealed that ZnO NPs size and shape are strongly dependent on the hydrolysis reaction time and addition of acetate counter ions, respectively. The change in shape and size has also affected the optical properties, such as the optical bandgap ( E g ) of ZnO NPs and their florescence.